Frecuencia genotípica para la presencia de TPA-25 en una población de estudiantes universitarios de Lima-Perú - Casas, Paola M. (2006)
The maín objectíve of this study was to evaluate the genotype frequency for the presence of the Alu TPA-25 insertíon in fue 8 intron of the tíssue plasminogen activator gene (TPA) in a population of 50 students belonging to the Faculty of Pharmacy and Biochemistry from the Universidad Nacional Mayor de San Marcos. It was used the Polimerase Chain Reaction (PCR) in order to amplify the region containing the Alu insertion and to determine the presence of TPA-25. The genotype frequency was determined by count of the presence or absence of the Alu insertion and then, evaluated across the test of Chi-square (X2) to know if they were in Hardy-Weinberg's balance. The genotype frequency for the presence of TPA-25 was in Hardy-Weínberg's balance (X2= 1.366, P = 0.505): homocigote 0.108, heterocigote 0.568 and homocigote absence 0.324. In conclusion, in the studied population exists a predominance of the heterocigote TPA-25 over the homocigote TPA- 25.